Computational investigation of a lifted hydrogen flame with LES and FGM. (15th April 2019) - Benim, Ali Cemal; Pfeiffelmann, Björn; Ocłoń, Paweł; Taler, Jan
Abstract: A numerical analysis of an atmospheric, subsonic, turbulent lifted H2 /N2 jet flame in vitiated co-flow is presented. Turbulence is treated by a Large Eddy Simulation (LES) methodology. As the turbulent combustion model, the Flamelet Generated Manifold (FGM) approach is used, which enables the incorporation of detailed chemistry via two additional scalar field variables. The results are compared with the measurements and with the predictions of other authors. It is observed that the achieved predictive capability is, in general, quite fair and comparable to that of alternative turbulent combustion models. This demonstrates the predictive capability of the FGM for this class of problems, and shows that the method, which is comparably very cost-effective in incorporating detailed combustion chemistry in turbulent flame calculations, can be applied, in combination with LES, to predict lifted hydrogen flames. Highlights: LES and FGM can be used to predict a lifted hydrogen flame with a fair accuracy. The lift-off height is under-predicted by about 10%. Premixed and diffusion combustion modes are encountered in the flame. Premixing dominated central zone is surrounded by diffusion dominated filaments.